Comparison of mental health outcomes of augmenting medications for patients with posttraumatic stress disorder: A national veterans affairs study. Issue 1 (16th June 2022) - Ranney, Rachel; Maguen, Shira; Woods, Anne; Seal, Karen H.; Neylan, Thomas C.; Bernardy, Nancy; Wiechers, Ilse; Ryder, Annie; Cohen, Beth E.
Abstract: Rationale: Posttraumatic stress disorder (PTSD) is highly prevalent among veterans. Many veterans with PTSD respond well to serotonin reuptake inhibitors (SRIs). Nonresponders may be prescribed augmenting medications, which are not as well‐studied in PTSD. Aims and Objectives: We used Veterans Health Administration electronic records to compare mental health outcomes (PTSD symptoms and rates of mental health hospitalizations and psychiatric emergency room visits) in patients with PTSD who were prescribed four different groups of augmenting medications (atypical antipsychotics, mirtazapine, prazosin or tricyclic antidepressants) in addition to SRIs—from the year before to the year after the start of the augmenting medication. Method: We included data from 169, 982 patients with a diagnosis of PTSD (excluding patients with comorbid bipolar or psychotic disorders) seen in Veterans Affairs care from 2007 to 2015 who were taking an SRI and filled a new prescription for one of the four augmenting medications for at least 60 days. Results: Patients evidenced minimal (<2%) reduction in PTSD symptoms and a larger reduction in psychiatric hospitalizations and psychiatric emergency room visits after receiving augmenting medications; this effect was largely similar across the four medication groups. Initiating augmenting medications was preceded by increases in PTSD symptoms, psychiatric hospitalizations and psychiatric emergency room visits. After initiating an augmenting medication, PTSD symptoms/hospitalizations/emergency room visits returned to baseline levels (before the start of the augmenting medication), but generally did not improve beyond baseline. Conclusion: Importantly, these effects could be explained by regression to the mean, additional interventions or confounding. These findings should be further explored with placebo controlled randomized clinical trials.